SPE Eastern Regional Meeting 2009
DOI: 10.2118/125525-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Geomechanics Of A Shale Play: What Makes A Shale Prospective!

Abstract: Many shale plays are being successfully developed throughout North America. These shale plays are being evaluated based on a number of criteria but primarily through typical unconventional and tight formation gas reservoir characteristics. Prospective shale plays share several interesting characteristics such as mineralogy, rock mechanics, and geomechanics. It is the intent of this paper to highlight and demonstrate the inter-relationship of these characteristics and show their importance on completion and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…Young's moduli for calibration, which may be 20-40% lower than (undrained) dynamic Emoduli (e.g., Yale and Jamieson, 1994;Britt and Schoeffler, 2009;Sone and Zoback, 2013a). …”
Section: Used Staticmentioning
confidence: 98%
See 1 more Smart Citation
“…Young's moduli for calibration, which may be 20-40% lower than (undrained) dynamic Emoduli (e.g., Yale and Jamieson, 1994;Britt and Schoeffler, 2009;Sone and Zoback, 2013a). …”
Section: Used Staticmentioning
confidence: 98%
“…Texas, Britt and Schoeffler (2009) concluded that prospective shales can be characterized solely by static Young's moduli higher than ≈24 GPa (3.5 Mpsi). In comparison, our estimate of E < 7-13 GPa for predominantly ductile shales is considerably lower than Britt and…”
Section: Comparison Of Brittleness Index Valuesmentioning
confidence: 99%
“…However these properties can also vary by a great margin. Most shale plays are actually fine-grained clastics and not necessarily shales (Britt and Schoeffler, 2009). In the case of this research, the Niobrara shale is mostly referred to as a limestone formation interbedded with shale beds.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of this research, the Niobrara shale is mostly referred to as a limestone formation interbedded with shale beds. Water-frac treatments are the common stimulation choice for most of the producing shale plays (Britt and Schoeffler, 2009). These formations also require optimized proppant selection.…”
Section: Introductionmentioning
confidence: 99%
“…Four samples were chosen: two from Embedment may cause a significant decrease of the fracture conductivity (Britt and Schoeffler, 2009).…”
Section: Methodsmentioning
confidence: 99%